At Home Versus in a Nursing Home: Long-Term Care Settings and Marginal Utility - Bertrand Achou; Philippe De Donder; Franca Glenzer; Minjoon Lee; Marie-Louise Leroux (Center for Economic Studies and ifo Institute (CESifo), 2023)
Marginal utility of financial resources when needing long-term care, and the related incentives for precautionary savings and insurance, may vary significantly by whether one receives care at home or in a nursing home. In this paper, we develop strategic survey questions to estimate those differences. All else equal, we find that the marginal utility is significantly higher when receiving care at home rather than in a nursing home. We then use these estimates within a quantitative life cycle model to evaluate the impact of the expected choice of care setting (home versus nursing home) on precautionary savings and insurance valuation. The estimated marginal utility differences imply a significant increase in the incentives to save when expecting to receive care at home. Larger incentives to self-insure also translate to a higher valuation of additional subsidies for home care than for nursing homes, shedding light on an efficient way to expand public long-term care subsidies. We also examine how the magnitude of our results quantitatively varies with the existing public long-term care subsidies.
Keywords: D14; E21; G51; I10; 330; long-term care; marginal utility; home care; nursing home; savings